The Impact of Consumer Psychological Needs in the New Era on Brand Marketing - Xue, Zhichao (International Journal of Social Sciences and Public Administration, 2024)
For the commodity brand, how to adapt to the development of the economic environment is extremely important, the consumer psychology is the key to the marketing strategy, is to adapt to the changes in the economic environment is an important factor, so the commodity brand is only practical based on the needs of the consumer’s psychology, do a good job of marketing the brand, should fit in the Under the current requirements of consumer culture, cultivate a new relationship between brands and consumers, under this condition, in order to effectively promote the brand better marketing.